Nutrient cycling in integrated rangeland/cropland systems of the Sahel - Powell, J.M.; Fernández Rivera, S.; Hiernaux, Pierre H.Y.; Turner, M.D. (Elsevier, 1996)
In the Sahel of West Africa, the productivities of rangelands, croplands and livestock are inextricably linked. Cattle, sheep and goats graze rangelands and crop residues, and their manure/urine is used to fertilize crops. Rangelands provide important feeds during the manuring period, resulting in a net nutrient transfer from rangelands to croplands. This paper examines the sustainability of nutrient transfers in integrated rangeland/cropland systems of the Sahel by examining the impact of grazing on rangeland vegetation structure and floristic composition, the impact of livestock on nutrient balances of rangelands and croplands, and the role of livestock in offsetting nutrient deficits through manuring. Rangeland nutrient balances are in equilibrium (inputs = offtakes) whereas croplands lack the internal capacity to replenish nutrient offtakes in grain (as food) and crop residues (as feed). Although soil nutrient mining is of general concern for the Sahel, local management practices of some farmers (e.g. corralling animals over-night on fields between cropping seasons, use of fertilizers) offset cropland nutrient deficits. The number of additional livestock, and their feed requirements needed to supply sufficient manure to offset cropland nutrient deficits, depend on rangeland and cropland productivity, livestock production goals, and management strategies of farmers. Livestock must be managed so they do not deplete the nutrient supply of rangelands in order to increase the manure supply for improving cropland productivity. Sustained rangeland productivity in the Sahel will depend largely on producing alternative feeds derived mostly from croplands. Land use and tenure policies that inhibit livestock mobility and, therefore, farmers' access to the manure of pastoralists herds, will greatly undermine the resilience of Sahelian rangelands, and increase the need for other external nutrient inputs such as fertilizers to prevent declines in soil fertility and crop yields.